Analisis Layout Surat Kabar berdasarkan Prinsip-Prinsip Desain melalui Metode Estetika Birkhoff - Kurnianto, Arik (Bina Nusantara University, 2013)
This study has primary focus to analyze the aesthetic layout of a newspaper with a mathematical approach, which refers to some methods of Birkhoff’s aesthetic measurement developed by David Ngo Chek Ling, et.al. Ngo developed a method of measuring the aesthetic layout that can be used for various design purposes, especially for a computer interface design. Measurement method that he developed refers to the principles of design aesthetics, such as: the principle of balance, the principle of sequence, the principle of unity, and the principle of equilibrium. Birkhoff aesthetic measurement method was used as final analysis to determine the value of aesthetic layout. In this study, some national and local media were selected as samples to determine and assess the aesthetic layout. Based on data analysis, Birkhoff aesthetic measurement method can be applied to measure the aesthetic value of the newspaper layout mathematically.